2023
DOI: 10.1007/s43390-023-00647-4
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-only correction surgery for idiopathic scoliosis Lenke type 5c: differences of strategies and outcomes between adult patients and adolescent patients

Abstract: Purpose To compare radiographic parameters, and functional and surgical outcomes between lumbar adolescent idiopathic scoliosis (AIS) and lumbar adult idiopathic scoliosis (AdIS). Methods A retrospective study was performed to identify Lenke 5c type AIS and AdIS patients from our scoliosis database who had undergone posterior surgical treatment for scoliosis. Preoperative and postoperative radiographic and clinical outcomes were compared between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Therefore, this study primarily focuses on comparative analysis at a 40mm displacement. Pan et al [31], through a retrospective analysis comparing correction outcomes of Lenke 5c type AIS and Adult Idiopathic Scoliosis (AdIS), found that the correction rate for AIS was 79.1% ± 13.2, while for AdIS, it was 65.6% ± 15.7. Yang et al [32], using titanium and cobalt-chromium alloy for adolescent idiopathic scoliosis correction, found that the correction rate for thoracic curvature was 71.2% in the titanium group and 66.8% in the lumbar curvature, whereas in the cobalt-chromium alloy group, the thoracic and lumbar correction rates were 71.2% and 73.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study primarily focuses on comparative analysis at a 40mm displacement. Pan et al [31], through a retrospective analysis comparing correction outcomes of Lenke 5c type AIS and Adult Idiopathic Scoliosis (AdIS), found that the correction rate for AIS was 79.1% ± 13.2, while for AdIS, it was 65.6% ± 15.7. Yang et al [32], using titanium and cobalt-chromium alloy for adolescent idiopathic scoliosis correction, found that the correction rate for thoracic curvature was 71.2% in the titanium group and 66.8% in the lumbar curvature, whereas in the cobalt-chromium alloy group, the thoracic and lumbar correction rates were 71.2% and 73.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in restrictions in daily activities, such as difficulties in walking, exercising, and socializing. Surgery tends to be more painful for adult patients compared to adolescents, but long-term outcomes show a significant reduction in pain regardless ( 54 ).…”
Section: Management Of Ais In Adultsmentioning
confidence: 99%
“…On the other hand, patients with severe AIS, particularly with curves greater than 50°, note significant limitations in activities of daily living and physical functioning. Surgical treatment in this population can prevent and alleviate these conditions, with treated adults showing significant improvements in their physical functioning ( 54 ). Such restoration in functional mobility can also improve performance at work, reducing absenteeism and increasing productivity by 18.1% post-surgical intervention ( 56 ).…”
Section: Management Of Ais In Adultsmentioning
confidence: 99%